Population structure and reproduction of Heimyscus fumosus (Brosset et al., 1965) in south-western Gabon - (:unkn) unknown (My University, 2003)
Population structure and annual reproduction cycle of the De B alsac's mouse (Heimyscus fumosus) were studied in a wild population of south-western Gabon. The reproductive status of the mice was investigated at autopsy, and age of each animal was estimated by tooth wear patterns and body weight. Sex-ratio was equilibrated whatever the season and the ageclass. Females tended to reach sexual maturity more slowly than males. However, the average age at puberty differed between individuals of the same sex. A wide range of tooth-wearclasses and weight-classes were present in most months of the year, and sexually active individuals of both sexes were captured in most months. However pregnant or lactating females were only captured from August to March, while very young individuals were only captured from October to March. Thus, the reproduction of H. fumosus would be partly seasonal with an interruption from April to July (end of the short wet season, and beginning of the long dry season). We discussed the potential role of food availability on this seasonality
Keywords: African Research